On the brink : how a crisis transformed Lloyd's of London - Duguid, Andrew; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Huge losses very nearly destroyed Lloyd's, a revered British institution, the world's largest insurance market. Ten thousand people faced big personal bills they thought profoundly unfair. They challenged a complacent institution, forcing it to confront its biggest ever crisis. This book tells what really happened, from the inside.
Keywords: Corporate governance; Corporations -- Finance; Investment banking; Securities; Insurance; Macroeconomics; Economic history